Rainfall-Runoff Study under Different Grasses Grown in Rainfed Sodic Black Clay Soil Condition - S R.S. Raghuwanshi; S.K.Verma; R.K. Sharma (Journal of Soil and Water Conservation, 2022)
In a field study five grass species viz. Marvel grass Dichanthium annulatum), Para grass (Brachiriamutica), Vetiver grass (vetiveria zizinoides), Karnal grass (Diplachne fusca) and Napier grass (Penisetum perpurium) were selected to asses their suitability for a moderate sodic black clay soil as biological reclaiming agent and vegetative barriers for reclaiming as well as reducing soil erosion. The study deals with recording rainfall and associated runoff during monsoon 2002-03 to 2004-05 alongwith survival percentage. The recorded rainfall-runoff data reveals order of suitability of grasses for controlling runoff as Marvel > Para > Vetiver > Karnal >Napier > Control with 3 - years average runoff values as 35.80%, 37.20 %, 39.36 %, 42.96 % and 48.66 % out of 3 - year average rainfall of 444.2 mm rainfall respectively. The study further reveals that the best-fitted equation were polynomials in case of all grasses like Marvel, Para, Vetiver, Karnal, Napier and Control with values as O.6771, 0.6906, 0.6294, 0.6647, 0.6237 and 0.6088 respectively . The graphical representations of predicted and observed values of runoff show reasonably close match in all the grasses. Hence the Here rainfall-runoff relationships can be successfully used for predicting runoff from recorded rainfall in case of various grasses in sodic black clay soils. Among the grasses grown, Para and Marvel grasses observed mosttolerant with higher survival % as 94 and 87in sodic black clay soils. Napier, Vetiver and Karnal observed moderately tolerant with survival % as 72, 67 and 63. Panicum was observed non tolerant with 10% survival. Finally study concludes that Para and Marvel grasses are more suitable for controlling runoff and tolerant to sodic black clay soils condition.